2002
DOI: 10.1007/s00213-002-1218-8
|View full text |Cite
|
Sign up to set email alerts
|

Occupancy of brain serotonin transporters during treatment with paroxetine in patients with social phobia: a positron emission tomography study with [ 11 C]McN 5652

Abstract: The results of this study in an anxiety disorder sample are consistent with previously reported results in a depressed sample and suggest that paroxetine at therapeutic doses achieves very high occupancy levels of the SERT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
38
1
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 20 publications
11
38
1
1
Order By: Relevance
“…There was, however, one subject in whom the cerebellar V T remained unchanged when the graphical analysis of reversible binding of the TAC was performed (Table 2, subject 1). The reductions of the cerebellar V T of this investigation are in line with previous reports by Parsey et al (2006a) who found in a [ 11 C]DASB study 33% occupancy in cerebellar grey matter of subjects after an acute treatment with sertraline or by Kent et al (2002) who reported from a [ 11 C]McN5652 study of five subjects with social phobia a reduction of the cerebellar V T of 23%±12% after paroxetine treatment. However, these reductions appear to be higher than expected from a blockade of the specific binding of the radioligand in the cerebellum given that the specific binding of [ 3 H]citalopram in autoradiographic studies of porcine brain has been reported as only 2.3 pmol/g tissue in the cerebellum in comparison with 26 pmol/g tissue in the amygdaloid area (Kretzschmar et al, 2003).…”
Section: Discussionsupporting
confidence: 91%
“…There was, however, one subject in whom the cerebellar V T remained unchanged when the graphical analysis of reversible binding of the TAC was performed (Table 2, subject 1). The reductions of the cerebellar V T of this investigation are in line with previous reports by Parsey et al (2006a) who found in a [ 11 C]DASB study 33% occupancy in cerebellar grey matter of subjects after an acute treatment with sertraline or by Kent et al (2002) who reported from a [ 11 C]McN5652 study of five subjects with social phobia a reduction of the cerebellar V T of 23%±12% after paroxetine treatment. However, these reductions appear to be higher than expected from a blockade of the specific binding of the radioligand in the cerebellum given that the specific binding of [ 3 H]citalopram in autoradiographic studies of porcine brain has been reported as only 2.3 pmol/g tissue in the cerebellum in comparison with 26 pmol/g tissue in the amygdaloid area (Kretzschmar et al, 2003).…”
Section: Discussionsupporting
confidence: 91%
“…This suggests a similar mode of action of these medication groups in serotonergic neurons. These findings are in line with results from PET studies on SERT occupancy using the selective ligands [ 11 C]DASB and [ 11 C]( + )McN5652 in major depression, social phobia and healthy volunteers showing similar degrees of SERT occupancy with SSRIs and clomipramine (Meyer et al, 2001;Kent et al, 2002;Suhara et al, 2003;Meyer et al, 2004). However, rates of SERT occupancy measured with these selective ligands are higher (about 80%) than those measured with b-CIT SPECT, which may be explained by the non-selectivity of b-CIT and contribution of dopamine and norepinephrine transporter binding to the signal measured in SERT-rich brain regions (for review see Meyer, 2007).…”
Section: Discussionsupporting
confidence: 87%
“…The cerebellum (especially the vermis) contains small amounts of SERT [43,44], which could result in an underestimation of BP ND in patients and healthy controls, expected to be 7% at most [45]. [ 123 I]β-CIT binds in vivo to SERT, DAT and norepinephrine transporters.…”
Section: Methodological Explanations For Inconsistent Findingsmentioning
confidence: 99%